Inovasi Produk Veggie Rice Roll Berbahan Dasar Beras Merah Dan Daun Leilem Bumbu RW - Tulandi, Dea Fitri; Lagarense, Bet El Silisna; Wewengkang, Silvana A (PolimdoSains, 2024)
Abstract: The product of Veggie Rice Roll is a variation of food made in the form of a round roll containing rice and vegetables. The rice used in the Veggie Rice Roll is brown rice as a substitute for white rice, considering its nutritional advantages such as fiber, vitamins, minerals, and antioxidants. The author uses brown rice as the main ingredient because brown rice is suitable for vegetarians because it has a high fiber content so that it can help make you feel full for longer and also helps regulate hormones involved in appetite control so as to reduce hunger hormone levels and is good for consumers who are on a diet. Along with the development of information about food and culinary, many people still maintain food from each region with the taste and characteristics of each region, so the author conducted this research by using leilem leaves to utilize leilem leaves (Clerodendrum minahassae Teysm. & Binn), which is commonly used in traditional cuisine in North Sulawesi, as one of the filling ingredients. Leilem leaves provide a distinctive taste and are highly nutritious in order to utilize typical Minahasa plants combined with RW spices, RW is short for the word rintek wu'uk (Minahasa language), which means hair or fluff. RW seasoning is usually used with dog meat mixtures, but the author substitutes leilem leaves as a filling in RW seasoning. Thus, this research produces Veggie Rice Roll with brown rice and RW seasoned leilem leaf filling which is expected to be beneficial for readers, the community, and the culinary industry. Keywords: veggie rice roll, leilem leaves, rw seasoning Abstrak: Produk Veggie Rice Roll adalah variasi makanan yang dibuat berbentuk gulungan bulat yang didalamnya berisi beras dan sayur-sayuran. Beras yang digunakan pada Veggie Rice Roll adalah beras merah sebagai pengganti nasi putih, mengingat keunggulan gizi yang dimilikinya seperti kandungan serat, vitamin, mineral, dan antioksidan. Penulis menggunakan beras merah sebagai bahan utama karena beras merah cocok untuk kalangan vegetarian karena memiliki kandungan serat yang tinggi sehingga bisa membantu membuat rasa kenyang lebih lama dan juga membantu mengatur hormon yang terlibat dalam pengendalian nafsu makan sehingga mengurangi tingkat hormon kelaparan dan bagus untuk konsumen yang sedang melakukan diet. Seiring dengan perkembangan informasi tentang makanan dan kuliner, banyak orang tetap mempertahankan makanan dari setiap daerah masing-masing dengan cita rasa dan khas dari setiap daerah, maka penulis melakukan penelitian ini dengan menggunakan daun leilem untuk memanfaatkan daun leilem (Clerodendrum minahassae Teysm. & Binn), yang umum digunakan dalam masakan tradisional di Sulawesi Utara, sebagai salah satu bahan isian. Daun leilem memberikan cita rasa khas dan bernutrisi tinggi guna untuk memanfaatkan tumbuhan khas Minahasa yang dipadukan dengan bumbu RW, RW merupakan kependekan kata rintek wu'uk (bahasa Minahasa), yang artinya rambut atau bulu halus. Bumbu RW biasanya digunakan dengan campuran daging anjing namun penulis mengganti daun leilem sebagai isian pada bumbu RW. Dengan demikian, penelitian ini menghasilkan Veggie Rice Roll dengan beras merah dan isian daun leilem bumbu RW yang diharapkan dapat bermanfaat bagi pembaca, masyarakat, dan industri kuliner. Kata Kunci: veggie rice roll, daun leilem, bumbu RW